Wheat grain yield prediction in the subhumid dry pampean region based on different weather indices (Semiárida, 2020)
The bread wheat is the most important winter crop in the subhumid dry Pampa region, but it has great interannual variability in grain yield. The objective this work was to predict the grain yield and the response to the aggregate of nitrogen fertilizer, based on different climate indices in the autumn prior to sowing. The trials were performed for a period of 22 years in the Agronomy Faculty of the UNLPam (36° 32' 49" S; 64° 18' 20" W). The fertilized treatment was added 100 kg.ha-1 of broadcast urea in early tillering. Climatic indexes were used for prediction; ONI (Ocean Child index), MEI (multivariate ENSO index) and TSA (Tropical South Atlantic). The MEI index of MarchApril and the ONI index of FebruaryMarchApril did not explain the grain yield. There was a negative relationship between the SST index (sea surface temperature) of March in zone 6.1 of the Atlantic Ocean (5° and 25°S, 0° and 20° W) with the grain yield and also with the response to the fertilizer aggregate. As the index increased, the grain yield and response to the aggregate of fertilizer decreased. This could beincorporated in the decision models prior of the sowing of wheat to estimate the achievable yields and also to improve the models of response to nitrogen fertilization in the region.
Keywords: Triticum aestivum; prediction; yield; nitrogen response